2016
DOI: 10.3109/03639045.2016.1160102
|View full text |Cite
|
Sign up to set email alerts
|

Development of a taste-masked oral suspension of clindamycin HCl using ion exchange resin Amberlite IRP 69 for use in pediatrics

Abstract: Clindamycin/resin complexation has shown to be an efficient method to mask the taste of clindamycin and was developed into a suspension formulation that can be used in pediatrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The palatability of BZL liquid formulation was also determined in a randomised study by six healthy human volunteers in an intake and spit test . The bitterness level of placebo cherry flavour solution (sample A) was recorded against the BZL final formulation (sample B) and the optimised BZL co‐solvent solution (sample C) using a numerical scale . As seen in Figure , the placebo formulation and the flavoured BZL final solution displayed scores between 0 and 2, which suggested that the final formulation was slightly bitter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The palatability of BZL liquid formulation was also determined in a randomised study by six healthy human volunteers in an intake and spit test . The bitterness level of placebo cherry flavour solution (sample A) was recorded against the BZL final formulation (sample B) and the optimised BZL co‐solvent solution (sample C) using a numerical scale . As seen in Figure , the placebo formulation and the flavoured BZL final solution displayed scores between 0 and 2, which suggested that the final formulation was slightly bitter.…”
Section: Resultsmentioning
confidence: 99%
“…They were asked to record the bitterness score through a numerical scale between 0 and 4, where 0, 1, 2, 3 and 4 were not bitter, slightly bitter, moderately bitter, bitter and very bitter, respectively. A final score of bitterness was calculated by the average of the value measured for each sample . The protocol of this assay was reviewed and approved by the Bioethics Committee of the National University of Rosario (Argentina) according to the Declaration of Helsinki.…”
Section: Taste Masking Analysismentioning
confidence: 99%
“…This can be explained by the good dispersibility of powder in presence of MD, as stated earlier. Another reason could be possible masking of the astringent flavour of Dillenia indica juice by MD, which has often been reported to mask undesirable flavours and odours during spray drying (Abraham & Mathew, 2013;Alayoubi et al, 2016;Bertelsen, Laursen, Knudsen, Møller, & Kidmose, 2018).…”
Section: B = MDmentioning
confidence: 99%
“…Besides the foremost and simplest approach of adding sweeteners and/or flavors, other taste-masking techniques have also been developed, such as coating drug particles with polymers, forming inclusion complexes, using ion-exchange resins, producing multiparticulate taste-masking systems with lipids by hot-melting extrusion, and so forth (51)(52)(53)(54)(55)(56)(57). As a whole, modification of microparticles based on particle engineering, especially forming a core-shell or embedded structure, occupies an indispensable status.…”
Section: Taste Maskingmentioning
confidence: 99%